SUPPLY CHAIN INNOVATION BOLSTERED UP BY SUPPLY CHAIN MODEL - Nur Fathin Nadira Abdul Rasib (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
The purpose of this study was to examine the level and relationship between supply chain management practices (SCMP), competitive advantage (CA), and supply chain innovation (SCI) among manufacturing firms in Malaysia. Giri and Bardhan (2015) found out that supply chain process becomes inefficient and lack business strategies has affect the operation which led to poor profitability. That’s why manufacturing supply chain needs to innovate constantly for maintaining their position in the marketplace and to fight uncertainties. Hence firms are focusing on strategies for developing innovation within and across its manufacturing supply chain. In line with following objectives, this study employed a quantitative research approach that utilized stratified sampling technique and self-administered questionnaire survey. The respondents for this survey were the senior managers (top management) in operations management from manufacturing firms in Malaysia. Subsequently, the survey data have been utilized to test the research framework and hypothesis. The results of the study are useful for supply chain practitioners and manufacturers in integrating the right SCMPs and competitive advantage on improving SCI. Furthermore, industrial practitioners also receive insight on how to take account of the mediating effect of competitive advantage in designing their supply chain innovation for better manufacturing performance. In fact, organizations are not certain of what to implement, due to a lack of understanding of what constitute a comprehensive set of SCMPs. There was far too little knowledge available on the role of competitive advantage in mediating the effect between SCMPs and supply chain innovation. As such, this paper is one of the first to address the mediating effect of competitive advantage between SCMPs and supply chain innovation. Also, the results have suggested successful dimensions of SCMPs that could be implemented in order to obtain competitive advantage and foster supply chain innovation in manufacturing industry in Malaysia.